Modular multilevel converter (MMC) based STATCOM with vector control and virtual impedance voltage compensations - Lawan, Abdurrahman Umar; Almurib, Haider A.F.; Khor, Jeen G. (Institute of Advanced Engineering and Science, 2019)
This paper presents modular multilevel converter (MMC) with circulating current control which provides an improved balanced capacitors voltages. The control is achieved by employing compensation techniques in the external and internal controls of the MMC based static compensator (STATCOM). Performance variations arise during STATCOM non-ideal operation with grid externally and during capacitors voltage transients due to charging and discharging within the MMC that result in the emergence of a voltage disturbance. The proportional integral (PI) controller is usually employed in the external and internal controls for a fast response and reactive current control. In this paper, the performance of the PI controller is improved using voltage compensation in the external control and virtual impedance in the capacitor voltage control within a five-level MMC. The proposed control minimizes the variations in the STATCOM operations with the grid and within the MMC to provide an enhanced overall system response.